Experimental study of properties for sand bricks with clinker as partial replacement for fine aggregate with ratio of 10% with rice husk of 10% , 20 % and 30% - Muhammad Nasaii, Mohd Zamri (2019)
Utilizing waste material in the construction industry is an effective way to protect the environment and minimize construction cost. In this paper, palm oil clinker (POC) aggregates and rice husk were used as fine aggregate replacement in sand brick production. Thus, experimental work has been conducted to investigate the effect of POC content and rice husk as partial sand replacement on the properties of brick. A total of three mixes containing various percentage of rice husk, which are 10%, 20%, 30% with constant 10% POC have been prepared. Half of specimens were water cured and another half were air cured until the testing date. The compressive strength test and flexural strength test was conducted at 28, 60 and 90 days. The water absorption test and density test was conducted at 28 days. The findings show that the more percentage of rice husk will reduce both compressive strength and flexural strength of the brick.